SALIVA AS A DIAGNOSTIC MEDIUM - Pink, Richard; Simek, Jiri; Vondrakova, Jana; Faber, Edgar; Michl, Petr; Pazdera, Jindrich; Indrak, Karel (Biomedical papers, 2009)
Background: This is a review of current knowledge on the use of saliva, gingival cervical fluid and mucosal transudate in the detection of some oral and systemic diseases as well as drugs. Oral fluid is a diagnostic medium that can be easily collected and with minimal invasion but it has been neglected in the past. Today, saliva is being used more often to diagnose: HIV virus, oro-facial and systemic tumors, cardiovascular disease and in detecting addictive substances. Neutropil levels in saliva may also indicate successful bone marrow transplant. Oral fluid is now systematically being researched and oral fluid analysis is being compared with the analysis of other diagnostic media such as blood and urine . A number of recent studies have focused on oncogenic marker detection and its monitoring in saliva. The latest clinical and laboratory findings on diagnostic markers of oropharyngeal carcinoma in oral fluid could be the beginning of their wider use as a diagnostic medium. Oral fluid can also be also used to diagnose other malignancies such as breast cancer which was one of the first malignant tumors to be detected using genetic protein biomarkers. Raised levels of CA15-3 and the epidermal growth factor (EGF) receptor have been found in patients with breast cancer and elevated levels of CA 125 and the glycoprotein complex in the saliva of ovarian cancer patients.Conclusion: Doubtless, the diagnostic value of saliva, aided by current technological development will increase rapidly in the near future.
Keywords: Keywords: Saliva/Biomarkers/Diagnostics